Phylogenetic and taxonomic revisions of Jurassic sea stars support a delayed evolutionary origin of the Asteriidae - Fau, Marine; Wright, David F.; Ewin, Timothy A.M.; Gale, Andrew S.; Villier, Loïc (PeerJ, 2024)
Background The superorder Forcipulatacea is a major clade of sea stars with approximately 400 extant species across three orders (Forcipulatida, Brisingida, Zorocallida). Over the past century, the systematics of Forcipulatacea have undergone multiple revisions by various authors, with some considering numerous families such as Asteriidae, Zoroasteridae, Pedicellasteridae, Stichasteridae, Heliasteridae, Labidiasteridae, and Neomorphasteridae, while others recognized only two families (i.e., Asteriidae and Zoroasteridae). Recent molecular analyses have shown the artificial nature of some of these groupings. Notably, four well-supported clades (Zorocallida, Brisingida, Stichasteridae, and Asteriidae) emerged from a synthesis of morphological and molecular evidence. The majority of extinct forcipulatacean species have been placed in modern families. However, many of these fossil species are in need of revision, especially those species placed within the Asteriidae, the largest of all forcipulatacean families. Methods In light of recent advancements in forcipulatacean systematics, we comprehensively reassess six well-preserved Jurassic forcipulatacean taxa, including the earliest crown-group members from the Hettangian (∼201.4 Ma), and also describe two new Jurassic genera, Forbesasterias gen. nov. and Marbleaster gen. nov. We assembled the largest and most comprehensive phylogenetic matrix for this group, sampling 42 fossil and extant forcipulatacean species for 120 morphological characters. To infer phylogenetic relationships and construct an evolutionary timeline for the diversification of major clades, we conducted a Bayesian tip-dating analysis incorporating the fossilized birth-death process. A total of 13 fossil species were sampled in our analysis, including six taxonomically revaluated herein, two recently reappraised species from the Jurassic, and five additional species from the Cretaceous and Miocene. Results Contrary to prior assumptions, our results indicate that none of the Jurassic taxa investigated belong to Asteriidae or any other modern families, and instead represent stem-forcipulatids. Furthermore, our phylogenetic results suggest that Asteriidae likely originated during the late Cretaceous. Our findings highlight a greater early diversity within the Forcipulatacea than previously presumed, challenging existing perceptions of the evolutionary history of this significant clade of marine invertebrates.
Keywords: Phylogeny; Jurassic; Asteroidea; Echinodermata; Forcipulatacea; Taxonomy; New taxon